Impact on the Sales of Cultural Sarees due to Imports from Inbound Mergers in the South India by Product Interrelations - Leelesh Sundaram; Selva Muthu (Journal La Bisecoman, 2022)
Existing studies have demonstrated the negativity of cultural distance in international investments more particularly in the case of inbound mergers across the globe. It is famous speculation that the increasing import of foreign products would certainly affect the use and value of cultural goods of the particular state or nation, due to various influencing factors like consumer temperaments, choice and arousals. In this hypothetical situation, various governments across the globe have started imposing restrictions and authoritative conditions on Inbound Mergers thereby curtailing the scope of further business. When a closer study in respect of Indian trade and culture is carried out, it is quite interesting to note that there are no significant findings on the impact of cross-border inbound mergers on cultural sarees in India. This existing ambiguity appears even more substantial in the case of Southern States as this part of the country is often known for their cultural values and existing cultural sarees at the same time the Inbound Mergers in the said geographical jurisdiction is also increasing. Hence in order to address this ambiguity, this study is carried out so as to find out the Impact of cultural sarees on Inbound mergers in the Southern States of India as it is necessary to identify if there is an adverse impact on sales rate of cultural sarees. Further, this impact might be due to various factors, in order to bring in a regulation or change in law, it is essential to figure out if there is product interrelations.